2020
DOI: 10.3390/universe6040048
|View full text |Cite
|
Sign up to set email alerts
|

Stable Wormholes in the Background of an Exponential f(R) Gravity

Abstract: The current paper is devoted to investigating wormhole solutions with an exponential gravity model in the background of f ( R ) theory. Spherically symmetric static spacetime geometry is chosen to explore wormhole solutions with anisotropic fluid source. The behavior of the traceless matter is studied by employing a particular equation of state to describe the important properties of the shape-function of the wormhole geometry. Furthermore, the energy conditions and stability analysis are done for two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Figure 2 provides the graphical analysis of (b s (r)/r) ⟶ 0 as r ⟶ ∞, which is not observed clearly. It shows that the wormhole geometry is not asymptotically flat, and this conduct agrees with the already prevailing cases described in the literature (see, for example, [43][44][45][46]). In the reference of energy conditions, it is verified from Figure 3 that the condition (ρ + P r ) is seen negative, which shows the presence of exotic matter.…”
Section: Advances In Astronomysupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 2 provides the graphical analysis of (b s (r)/r) ⟶ 0 as r ⟶ ∞, which is not observed clearly. It shows that the wormhole geometry is not asymptotically flat, and this conduct agrees with the already prevailing cases described in the literature (see, for example, [43][44][45][46]). In the reference of energy conditions, it is verified from Figure 3 that the condition (ρ + P r ) is seen negative, which shows the presence of exotic matter.…”
Section: Advances In Astronomysupporting
confidence: 90%
“…In the literature, many researchers studied the actuality of wormhole solutions by using different kinds of exotic matter in the context of different modified theories and also tested their stability [42][43][44][45]. Recently, Mustafa et al [46] found the stable wormhole solutions for the exponential gravity model in the f(R) gravity. Samanta and Godani [47] analyze the traversable wormhole solutions with exponential shape function in modified gravity.…”
Section: Introductionmentioning
confidence: 99%
“…[ 18–26 ] In a recent work physically viable wormhole solutions in the f(R) theory of gravity with exponential model have been discussed by Mustafa et al. [ 30 ] Recently, Falco et al. have discussed the wormhole solutions through the Poynting‐Robertson effect.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Classical works comprising the modified theory of f (R) gravity by Capozziello et al can be found in the literature. [18][19][20][21][22][23][24][25][26] In a recent work physically viable wormhole solutions in the f (R) theory of gravity with exponential model have been discussed by Mustafa et al [30] Recently, Falco et al have discussed the wormhole solutions through the Poynting-Robertson effect. [27,28] Non-extremal spherically symmetric instanton wormhole solution in string theory have been discussed by Bergshoeff et al [31] Maldacena et al have presented a study of some traversable wormhole geometries in the background of AdS 2 gravity.…”
Section: Introductionmentioning
confidence: 99%
“…Dias and Lemos studied stability in higher dimensional Einstein gravity [32]. Thin-shell wormholes can also be constructed in extended gravity models [33][34][35] (see [36][37][38][39][40][41][42][43][44][45][46] for recent progress on thin-shell wormhole and its applications).…”
Section: Thin-shell Wormholesmentioning
confidence: 99%